Balanced Scorecard As A Tool For Measuring Employee Performance - Cedaryana, Cedaryana; Safria, Dhuha (Sean Institute, 2025)
This study examines the implementation of the Balanced Scorecard (BSC) at PT. DHF as a tool to measure employee performance, which is crucial for improving organizational efficiency and effectiveness. Using a qualitative case study approach, data were collected through in-depth interviews with management and employees, as well as internal document analysis. Overall, the study demonstrates that the implementation of the Balanced Scorecard method can serve as an effective tool for measuring employee performance at PT. DHF. The implications of these findings highlight the importance of considering multiple perspectives in performance measurement to achieve sustainable competitive advantage, with this study focusing on the learning and growth perspective. However, the study also revealed a low level of employee motivation at PT. DHF. This suggests that although the BSC is effective in measuring performance, other factors, such as employee motivation, also play a significant role in achieving optimal performance.